Nursing students’ perceptions following the enactment of the Spanish Euthanasia Law - Arreciado Marañón, Antonia (Nursing ethics, 2026)
Background Little is known about nursing students? perceptions of euthanasia and their future role in the process, especially in Spain, where the Euthanasia Regulation Law was enacted relatively recently (2021).Aim (I) To explore fourth-year nursing students? perceptions of euthanasia following its legalization in Spain; (II) To explore how nursing students envision their future professional role in the euthanasia process.Research Design Qualitative descriptive study.Participants and research context The study was conducted at the nursing school of a public university in Catalonia, Spain. Participants were fourth-year nursing students (2022-2023) selected through purposive sampling to ensure diverse profiles. Fourteen semi-structured individual interviews were conducted until data saturation was reached. The data were analyzed using a four-phase open coding procedure.Ethical Considerations Written informed consent was obtained from all participants. Respondent anonymity and data confidentiality were guaranteed. The study was approved by the Ethics Committee.Results Three categories emerged. (1) Theory and practice in euthanasia training. Students report having only limited theoretical and practical knowledge, which leaves them feeling insecure about facing these situations. Practical experience, observing professionals, and testimonies of suffering all contribute to ethical dilemmas and an evolving vision of life and death. (2) Recognizing autonomy in the context of euthanasia. Students identify multiple dimensions of autonomy, highlighting personal autonomy (the right to decide) as a fundamental principle. (3) Perception of future role. Students see their role primarily as supporting patients and families from within a multidisciplinary team.Conclusions Euthanasia education should be reinforced by integrating ethical and emotional reflection strategies and promoting the clinical practicum as a key learning environment. Multidisciplinary teamwork skills should be honed, especially shared decision-making. Nurses must play an active role in these processes to ensure a patient-centered and rights-based approach.